Combining Calcitonin and Procalcitonin and Rheumatoid Arthritis-Related Biomarkers Improve Diagnostic Outcomes in Early Rheumatoid Arthritis. (27th May 2021) - Liu, Yingwen; Shi, Jing; Wang, Bo; Zhou, Lijing; Zhou, Xiaolan; Du, Yane; Li, Dandan; Duan, Liang; Hu, Qin; Chen, Weixian; Li, Pu
Abstract : Objective . To demonstrate whether procalcitonin (PCT) combined with calcitonin (CT) could provide additional diagnostic value to other clinically available rheumatoid arthritis- (RA-) related biomarkers in the early diagnosis of RA. Method . The blood samples aseptically collected by venipuncture were centrifuged within 1 hour and frozen at -80°C. PCT and CT levels were measured using electrochemiluminescence immunoassay (ECLIA) in 260 subjects (48 patients with early RA, 34 patients with established RA, 37 patients with systemic lupus erythematosus, 30 with osteoarthritis, 31 with gouty arthritis, and 80 healthy participants). Anti-cyclic citrullinated peptide (Anti-CCP) and anti-RA33 antibodies (Anti-RA33) were analyzed by ELISA. RF was detected by transmission immunoturbidimetry. Mann–Whitney U tests and Kruskal-Wallis tests compared differences among groups. Spearman's rank correlation analysis determined the relationship between biomarkers. Receiver-operator characteristic (ROC) curves were generated, and diagnostic performance was assessed by area under the curve (AUC), as well as specificity, sensitivity, likelihood ratios (LR). Results . Median serum PCT concentrations were significantly higher (p < 0.0001 ) in patients with early RA (0.065 ng/ml) when compared with healthy controls (0.024 ng/ml), and patients with osteoarthritis (0.025 ng/ml). When compared with gouty arthritis (GA) controls (0.072 ng/ml) and systemic lupus erythematosus (SLE) controls (0.093 ng/ml), median serum PCT concentrations were not significant in patients with early RA (0.065 ng/ml). Median serum CT concentrations were significantly lower (p < 0.0001 ) in patients with early RA (0.880 pg/ml) compared with healthy controls (3.159 pg/ml), patients with SLE (2.480 pg/ml), and patients with GA (2.550 pg/ml). When compared with osteoarthritis controls (0.586 pg/ml), median serum CT concentrations were not significant in patients with early RA (0.880 pg/ml). ROC curve analysis comparing early RA with healthy controls demonstrated that the AUC of RF, anti-CCP, and anti-RA33 were 0.66, 0.73, and 0.64, respectively; the additions of PCT and CT further improved the diagnostic ability of early RA with the AUC of 0.97, 0.98, and 0.97, respectively (p < 0.01 ). The sensitivities of RF, anti-CCP, and anti-RA33 for early RA were 33.33%, 44.74%, and 58.33%, respectively, and the additions of PCT and CT showed very high sensitivities of 83.33%, 92.11%, and 87.50%. The high-value groups of PCT moderately correlated with the anti-RA33 levels (r = 0.417, p < 0.05 ). CT had no significant correlation with disease duration, radiographic progression, or clinical/serological variables, such as ESR levels, CRP levels, RF, anti-CCP, and anti-RA33 levels in early RA. Conclusions . Serum PCT and CT combined with clinically available RA-related biomarkers could further improve the diagnostic efficiency of early RA.